A case report of intramuscular abscess secondary to Epicoccum nigrum infection / Nurul Azira Mohd Shah ... [et al.] - Mohd Shah, Nurul Azira (Faculty of Medicine, 2015)
A 36-year-old man with underlying chronic lymphocytic leukemia had left arm swelling for a duration of 3 months. Clinically, the affected arm was swollen, erythematous and tender. Epicoccum nigrum was isolated from the culture of the tissue that was obtained intra-operatively. He was treated and responded to voriconazole therapy. To the best of our knowledge, this is the first case of intramuscular abscess as a result of E. nigrum infection in an immunocompromised patient.